Kidney function mediates the effects of four per-and polyfluoroalkyl substances (PFAS) on atherosclerotic cardiovascular disease - Zhengqi Wei; Keke Wei; Ming Yang; Ming Ying; Ziyue Yin; Na Wang; Lei Zhang (Ecotoxicology and Environmental Safety)
Background: PFAS pose a significant threat to cardiovascular health and increase the risk of atherosclerotic cardiovascular disease (ASCVD). However, there is limited research evidence regarding the mechanisms by which PFAS affect the risk of ASCVD and the exposure-risk (E-R) relationship. The effect of kidney function in the relationship between PFAS and ASCVD risk has not been adequately validated. Objective: This study aims to explore the mechanisms by which four PFAS (Perfluorooctanoic acid (PFOA), Perfluorooctanesulfonic acid (PFOS), Perfluorohexanesulfonic acid (PFHS), and Perfluorononanoic acid (PFNA)) affect the risk of ASCVD and to verify and discuss the mediating effect of kidney function in this impact. Methods: This study utilizes data from 14,607 participants in the NHANES 2005–2018 to conduct a cross-sectional study. Initially, Generalized Linear Model (GLM) and Restricted Cubic Splines models are used to assess the impact of four PFAS on ASCVD risk and the E-R relationship. Subsequently, the Weighted Quantile Sum regression (WQS) model is used to evaluate the relationship between mixed four PFAS exposure and ASCVD risk. Finally, Directed Acyclic Graphs (DAG) and causal mediation models are used to confirm and analyze whether the decline in kidney function mediates the impact of four PFAS on ASCVD risk. Results: The results from GLM and WQS models indicate that both singular and mixed four PFAS exposures are associated with an increased risk of ASCVD. The E-R curves between four PFAS singular and mixed exposures and ASCVD risk are all characterized by nonlinearity. The results from DAG and causal mediation models clearly indicate that the decline in kidney function plays a significant mediating role in the relationship between four PFAS and ASCVD risk. Conclusion: Exposure levels of four PFAS do not significantly increase the risk of ASCVD unless they reach a certain threshold, and the decline in kidney function exerts a significant mediating effect in the relationship between four PFAS exposure and ASCVD risk.